COMMUNITY PERCEPTION ON THE IMPLEMENTATION OF THE PUNISHMENT OF lashing IN WEST ACEH - Nur Anita; Adam Sani (SEAN Institute, 2022)
Caning in Aceh is a form of punishment regulated in the Qanun Jinayah. The implementation of caning has given rise to various public perceptions, namely that there are those who support it and some who do not agree with various reasons, both psychologically and for reasons of human rights. This study aims to determine the public's perception of the implementation of caning in West Aceh. This research was conducted using empirical methods, namely collecting data through observation, interviews and documentation, then analyzed and described in written form and words to draw conclusions. The results of the study show that from 2018 to 2021 in West Aceh Regency there were 77 (seventy-seven) cases of violations of the Jinayah Qanun which were lashed based on the Syari'iyah Court Decision.